An Indwelling Voice - Goldberg, Stuart (University of Toronto Press, 2024)
How have poets in recent centuries been able to inscribe recognizable and relatively stable sincere voices despite the wearing of poetic language and reader awareness of sincerity’s pitfalls? How are readers able to recognize sincerity at all given the mutability of sincere voices and the unavailability of inner worlds? What do disagreements about the sincerity of texts and authors tell us about competing conceptualizations of sincerity? And how has sincere expression in one particular, illustrative context – Russian poetry – both changed and remained constant? An Indwelling Voice grapples, uniquely, with such questions. In case studies ranging from the late neoclassical period to post-postmodernism, it explores how Russian poets have generated the pragmatic framings and poetic devices that allow them to inscribe sincere voices in their poetry. Engaging Anglo-American and European literature, as well as providing close readings of Russian poetry, An Indwelling Voice helps us understand how poets have at times generated a powerful sense of presence, intimating that they speak through the poem.